An enhanced water index in extracting water bodies from Landsat TM imagery. Issue 3 (3rd July 2017) - Yang, Jason; Du, Xianrong
ABSTRACT: This paper combines the principal component analysis (PCA) with a modified normalized difference water index (MNDWI) to improve the accuracy in extracting water bodies from Landsat Thematic Mapper (TM) imagery. To this end, one Landsat TM image of Taiyuan, China, obtained on 23 September 2011 was used to perform PCA and extract MNDWI. The first two principal components of the PCA and extracted MNDWI were combined to compose a false-colour image, which was then used to develop the enhanced water index (EWI). This method was applied to extract water bodies from Landsat TM imagery for both urban areas and surrounding mountain areas of Taiyuan, which resulted in an overall accuracy of 95%. EWI was also compared with other common water indices in extracting water bodies including general water index, MNDWI and new water index. The results show that the proposed method has the highest accuracy and is recommended to extract water bodies using multispectral satellite imagery for urban areas with mountains surrounded.